A Study on Tourism Development - Vinay Raj R (AG Volumes, 2021)
The primary focus of this research is on the in-depth examination of Indian tourists. Indian tourism industries is growing rapidly in the last several years, making a considerable contribution to the growth of the country’s GDP, foreign exchange earnings, and employment opportunities across all of these metrics. India has a lot to offer tourists in terms of rich culture and natural beauty, making it an obvious choice for tourism promotion. Government of the India initiatives to boost tourism have been in place for some time now. Tourism is indeed a growth-oriented business that has a significant influence on the government’s employment as well as foreign currency opportunities. Tourism development is examined from the beginning to the most current advancements in this article.